2019
DOI: 10.1186/s40246-019-0231-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide association study of multiple myeloma identifies candidate susceptibility genes

Abstract: Background: While genome-wide association studies (GWAS) of multiple myeloma (MM) have identified variants at 23 regions influencing risk, the genes underlying these associations are largely unknown. To identify candidate causal genes at these regions and search for novel risk regions, we performed a multi-tissue transcriptome-wide association study (TWAS). Results: GWAS data on 7319 MM cases and 234,385 controls was integrated with Genotype-Tissue Expression Project (GTEx) data assayed in 48 tissues (sample s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The association of AID/APOBEC proteins with the formation of a tumor clone may be direct, through mutations in the deaminase gene leading to an increase in its activity. The role of mutations in the APOBEC3 genes (paralogs C, D, F, G, and H) in the pathogenesis of multiple myeloma has been revealed [69]; mutations in the genes of deaminases can increase their mutagenic potential in tumors. The appearance of single nucleotide polymorphisms and deletions in APOBEC3 genes correlates with an increased risk of developing bladder and breast cancer, respectively [70][71][72].…”
Section: Mechanisms Of Aid/apobec Expression Impairment In Tumorsmentioning
confidence: 99%
“…The association of AID/APOBEC proteins with the formation of a tumor clone may be direct, through mutations in the deaminase gene leading to an increase in its activity. The role of mutations in the APOBEC3 genes (paralogs C, D, F, G, and H) in the pathogenesis of multiple myeloma has been revealed [69]; mutations in the genes of deaminases can increase their mutagenic potential in tumors. The appearance of single nucleotide polymorphisms and deletions in APOBEC3 genes correlates with an increased risk of developing bladder and breast cancer, respectively [70][71][72].…”
Section: Mechanisms Of Aid/apobec Expression Impairment In Tumorsmentioning
confidence: 99%
“…In total, genes affecting several biological pathways have been tightened to MM development risk, including histone modification and chromatin remodeling, transcription, and co-transcriptional RNA maturation, IRF4-MYC regulatory network, B-cell differentiation, genome stability, and telomere maintenance (see Table S3 ). A recent approach taking advantage of a transcriptome-wide association study allowed for the expansion of GWAS analysis and identified new MM risk genes, including DNA/RNA-editing cytosine deaminases APOBEC3C , APOBEC3D , APOBEC3F , APOBEC3G, and APOBEC3H at 22q13.1, responsible for immunity, and RNF40 at 16p11.2, involved in DSB-repair [ 354 ].…”
Section: Predisposition To MMmentioning
confidence: 99%
“…The minor allele [A] of this SNP downregulates TERT promoter activity and has been associated with the increased breast and ovarian cancer but decreased risk of prostate cancer and MM [ 689 , 697 ]. Additionally, SNP rs10936600 is located in the same 3q26.2 locus and is associated with an increased risk of MM [ 354 ]. This SNP is located within the LRRC34 gene—a predicted ribonuclease inhibitor.…”
Section: Telomere Maintenance Pathways and MM Riskmentioning
confidence: 99%
“…Patients reclassified from standard-risk FISH to HR GEP presented with 1q amplification of equal to or over four copies [ 54 ]. Elsewhere, a multi-tissue transcriptome-wide association study (TWAS) aimed at exploring MM biology by Went et al [ 55 ] identified 108 genes at 13 independent regions associated with MM risk; all of these were within 1 Mb of known MM GWAS risk variants [ 56 , 57 , 58 , 59 ].…”
Section: Gene Expression Profile In Multiple Myeloma Biology and Prognosismentioning
confidence: 99%